Manajemen Sistem Asrama Madrasah Aliyah Boarding Berbasis Prinsip Pendidikan Islam: A Systematic Literature Review - Najma Khairunnisa; Mulyawan Safwandy Nugraha (Institut Agama Islam Hidayatullah Batam, 2026)
The management of boarding systems in Madrasah Aliyah (MA) Boarding plays a strategic role in supporting the achievement of holistic Islamic educational goals. This study aims to analyze and synthesize research findings on the management of MA Boarding dormitory systems based on Islamic educational principles through a Systematic Literature Review (SLR) approach. Literature was collected from reputable academic databases, including Google Scholar, Garuda, DOAJ, and Scopus, focusing on publications from 2020–2025. The selected studies were analyzed using content analysis and thematic synthesis techniques. The findings reveal that research on boarding school management is primarily concentrated on four themes: character education, management functions, organizational culture, and educational leadership. Effective dormitory management is achieved through the integration of planning, organizing, implementing, and controlling functions with Islamic values such as amanah (trustworthiness), shura (deliberation), justice, role modeling, and responsibility. The study also identifies key challenges related to human resource competence, institutional coordination, and digital transformation. The proposed conceptual model emphasizes the integration of managerial functions and Islamic educational values to strengthen students’ religious character, discipline, independence, and organizational culture. This study contributes to the development of Islamic educational management theory and provides practical guidance for improving the governance of MA Boarding institutions.